In vitro evaluation of pan-PI3-kinase inhibitor SF1126 in trastuzumab-sensitive and trastuzumab-resistant HER2-over-expressing breast cancer cells - Ozbay, Tuba (Springer-Verlag, 2009)
PURPOSE: The purpose of the current study is to determine the in vitro cytotoxic effects of the novel pan-PI3-kinase inhibitor SF1126 in HER2-over-expressing breast cancer cells. METHODS: Cell proliferation and cytotoxicity were examined by MTS colorimetric assay, FACS analysis, colony formation assay, and immunoblotting. Phosphoinositol-3-kinase signaling was assessed by immunoblotting for phosphorylated Akt. Combination effects of trastuzumab and SF1126 were examined in resistant cells by MTS and soft agar assay. RESULTS: SF1126 inhibited proliferation, and induced G1 arrest and apoptosis of SKBR3 and BT474 parental and trastuzumab-resistant HER2-over-expressing cells. Colony formation was inhibited by SF1126, caspase 3 and PARP proteins were cleaved, and survivin was down-regulated. Inhibition of PI3-kinase was confirmed by reduced phosphorylation of Akt. Finally, the combination of SF1126 and trastuzumab synergistically inhibited proliferation of resistant cells, with SF1126-treated cells showing reduced anchorage-independent growth. CONCLUSIONS: These results provide evidence that a clinically relevant pan-PI-3 kinase inhibitor can reverse trastuzumab resistance in breast cancer cells, and support further study of PI3-kinase inhibitor SF1126 in HER2-over-expressing breast cancer cells, including those that have progressed on trastuzumab.